2014
DOI: 10.1080/15389588.2014.927576
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Crash Patterns on Roundabouts

Abstract: The main goal of this study was to identify and analyze dominant crash types at roundabouts by taking into account detailed information on the crash location. Some connections between certain roundabout crash types, their crash location, and roundabout design characteristics have been found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…We chose to focus on these junctions rather than intersections, as some crashes still occur on the former. Moreover, as some dominantly occurring crash types on roundabouts such as rear-end crashes, entering-circulating crashes, and singlevehicle collisions occur at different parts of roundabouts [4], we examined five locations on roundabouts to assess drivers' behaviors.…”
Section: Eye Movement and Distracted Drivingmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to focus on these junctions rather than intersections, as some crashes still occur on the former. Moreover, as some dominantly occurring crash types on roundabouts such as rear-end crashes, entering-circulating crashes, and singlevehicle collisions occur at different parts of roundabouts [4], we examined five locations on roundabouts to assess drivers' behaviors.…”
Section: Eye Movement and Distracted Drivingmentioning
confidence: 99%
“…Similar results were presented in the annual crash reports provided by Spain's National Traffic Department (DGT), which stated that traffic accidents at roundabouts increased by 34% from 2012 to 2016 and that fatal accidents in these road junctions doubled during the same period [2]. Most traffic crashes that occur at roundabouts are entering/exiting circulating crashes, rear-end crashes, collisions with pedestrians and cyclists, and collisions with parts of roundabouts (e.g., central island, curb) [3,4]. Arndt and Troutbeck [3] reported that roughly 80% of traffic crashes at roundabouts take place on entry lanes, mostly because of a driver's failure to give the right of way to oncoming traffic or vulnerable road users [5].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the findings of this study result in a detailed description of the crash patterns at signalized intersections, which provide insights into the safety impact and possible safety issues of this intersection design. Other studies have also applied the same or similar methods to other locations including stop-sign-controlled intersections (21), roundabouts (22), freeway ramps (23), and work zone crashes (24).…”
Section: Study Objectivementioning
confidence: 99%
“…Prior studies have investigated various types of built environmental correlates of cycling injuries, and have studied the relative levels of risk associated with (1) various route and intersection types (e.g., major streets, local roads, roundabouts, and signalized vs. non-signalized intersections) (Reynolds et al, 2009;Zahabi et al, 2011;Teschke et al, 2012;Hollingworth et al, 2015;Kaplan and Giacomo Prato, 2015;Polders et al, 2015), (2) presence and types of cycling infrastructures (e.g., on-road shared cycling routes, marked bike lanes, separated cycle paths via barrier, etc.) (Reynolds et al, 2009;Teschke et al, 2012;Pedroso et al, 2016;Pucher and Buehler, 2016), (3) land uses (e.g., density of retail establishments, residential/population density, industrial density, and proximity to parks) (Wedagama et al, 2006;Zahabi et al, 2011;Romanow et al, 2012;Kaplan and Giacomo Prato, 2015;Chen and Shen, 2016), (4) environmental factors affecting levels of visibility (e.g., slope, street lighting, and sinuosity) (Zahabi et al, 2011;Dozza and Werneke, 2014;Chen and Shen, 2016), and (5) traffic volume and proportion of cyclists to total traffic (Vandenbulcke et al, 2009;Jacobsen, 2015;Kaplan and Giacomo Prato, 2015;Elvik and Bjørnskau, 2017).…”
Section: Introductionmentioning
confidence: 99%